Entrepreneurial Orientation and Intellectual Capital on Business Performance: The Mediating Role of Competitive Advantage - Ria Mujianti; Jauharo Putri Febriana; Sinta Anggraini; Uzlatul Faridah; Khamdan Suriyok (AIBPM Publisher, 2025)
Business development in traditional trading often encounters structural challenges, including slow service delivery and limited product innovation. This study investigates the effect of entrepreneurial orientation and intellectual capital on business performance, with competitive advantage as a mediating variable. Data were collected through interviews and surveys with traders under the guidance of the Pasuruan City Industry and Trade Service. Using a quantitative approach, the findings reveal that entrepreneurial orientation significantly improves business performance by fostering proactive strategies, innovation, and risk-taking behavior. In contrast, limited competitive advantage among traders, reflected in the lack of product differentiation and inability to exceed consumer expectations, constrains the overall growth of their businesses. Intellectual capital, encompassing human, structural, and relational capital, plays a complementary role in supporting entrepreneurial orientation to enhance business outcomes. This study highlights the importance of strengthening entrepreneurial orientation and developing intellectual capital to achieve sustainable business performance, offering both theoretical contributions and practical implications for micro and small traders in regional markets.